The Development of Sepak Takraw Skill Training Model Based on Drill Double Event in South Jakarta Club Takraw - Gani, Abdul (Journal of Education, Health and Sport, 2018)
This study aims to determine the needs of Sepak Takraw athletes in improving the skills through base on drill double event players in South Jakarta Club Takraw. In 2011, Indonesian Takraw team got gold medal in SEA Games, and in 2013 got silver medal. In the Singapore SEA Games, Indonesian Takraw team got only one bronze medal. Its decrease in Indonesian achievements in the sepak takraw branch in particular double event number. Based on the background, Sepak Takraw team need a training model program. The researcher analyzes the needs of players through an explanatory sequential mixed approach, namely conducting quantitative research with survey methods and then arranging detailed results through a qualitative approach. Qualitative data was obtained through observations during drill double event based Takraw playing skills. The researcher worked with 12 athletes by conducting interviews for 30 to 40 minutes. This study was conducted for 12 weeks. The results of this study indicate that the development of skills training model through guidebooks is said to be feasible to use in Takraw practice. An increase in service, smash and double event feedback. Sepak Takraw skill training based on drill double event model is effective and improves the skills of athletes. So that this research can be implemented in every training of Sepak Takraw players to improve the quality of the game.